Prognostic Analysis of EGFR-TKIs Combined with Gamma Knife in EGFR-mutant Lung Adenocarcinoma with Brain Metastasis - Limin CHEN; Mengjiao FU; Jianya ZHOU; Yinan YAO; Jianying ZHOU (Chinese Journal of Lung Cancer, 2019)
Background and objective Advanced epidermal growth factor receptor (EGFR)-mutant lung adenocarcinoma had a high overall incidence of brain metastasis during the full course, and local brain radiotherapy combined with systemic targeted therapy may be a better strategy. This study aimed to identify the prognostic factors of EGFR-mutant brain-metastatic lung adenocarcinoma patients who received EGFR-tyrosine kinase inhibitors (EGFR-TKIs) in combination with gamma knife radiosurgery. Methods Retrospective analysis of EGFR-mutant lung adenocarcinoma patients with brain metastases which developed at initial diagnosis or during EGFR-TKIs treatment period were performed. Intracranial progression free survival (PFS) was statistically analyzed between different subgroups to find out the prognostic factors including gender, age, smoking history, extracranial metastasis, EGFR mutation type, size and number of intracranial lesions, carcino-embryonic antigen (CEA) level, lung-molGPA score and so on. Results A total of 74 EGFR-mutant brain-metastatic lung adenocarcinoma patients were enrolled in this study, with median intracranial PFS of 14.7 months. One-year intracranial-progression-free rate was 58.5%, and two-year rate was 22.2%. Univariate survival analysis showed that patients with lower CEA level at initial diagnosis (<10 ng/L)(16.9 months vs 12.6 months, P=0.012) and smaller intracranial lesions (<2 cm)(15.4 months vs 10.8 months, P=0.021) and higher lung-molGPA score (>3)(15 months vs 12.6 months, P=0.041) were prone to have a superior intracranial PFS. Multivariate analysis showed that CEA≥10 ng/mL and intracranial lesion≥2 cm were the independent risk factors of intracranial PFS. Conclusion EGFR-TKIs in combination with gamma knife radiosurgery was an efficient treatment option to control the cranial tumor lesion. CEA≥10 μg/L at initial diagnosis and intracranial lesion≥2 cm were the risk factors of EGFR-mutant brain-metastatic lung adenocarcinoma patients receiving EGFR-TKIs in combination with gamma knife radiosurgery.